HYBRID SPACE AS A FORM OF SOCIAL ASPECT SUSTAINABILITY IN THE URBAN SPRAWL PHENOMENON (CASE STUDY: DARMO PERMAI AREA SURABAYA-INDONESIA) - Darmansjah Tjahja Prakasa; Bambang Soemardiono; Ima Defiana (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2022)
Urban sprawl is a phenomenon characterized by the accidental movement of residents from the downtown to the urban periphery. This urban sprawl phenomenon tends to hurt the urban boundary. The concept of spatial hybrid can indirectly be indicated as a form of sustainable urban development that overcomes the problems caused by the negative ImpactImpact of urban sprawl in the urban periphery. This study uses the constructivism paradigm. The strategy in this research is a combination of qualitative research and case studies. It specifically selected case studies in the area of Darmo Permai Surabaya-Indonesia. The Darmo Permai area is a form of urban sprawl that began in 1973. The Darmo Permai area finds harmony between the newcomer and residents through an adaptation process. This harmony is manifested in a hybrid space analyzed from the social aspect of sustainability. The hybrid space is founded based on the activities of its residents, which are characterized by five aspects of the hybrid space. The five aspects of the hybrid space are coexistence, transfusion, interconnection, ambivalence, and heterogeneity.